Empowering Digital Transformation through AI, Big Data and Cloud Computing in Ethical Way for Electronic Health Record Management - B.V., Manjunatha; Kumar, Manish (Nepalese Journal of Management Science and Research, 2025)
Empowering Digital transformation in healthcare organizations is bringing a fresh perspective for healthcare delivery. Digital transformation can create innovative healthcare systems that increase access and consistency of patients care with automation, security and data driven insights. One such insight is EHR system. A patient's medical record stored digitally is called an Electronic Health Record (EHR). In this research paper, we are suggesting a centralized electronic patient file management system and a system Architecture for EHR in place of a paperback system. The proposed EHR system contains every healthcare providers such as hospitals, pharmacies, laboratories, health insurance companies, private clinics under a single system where all the data is stored and accessed by the relevant authorities. However, it has some shortcomings in terms of storage, security, and privacy. We are therefore suggesting a system that combines cloud computing, artificial intelligence, and big data to address these shortcomings. Security and privacy will be guaranteed by storing patient records on a Cloud from the time before birth until after death. All these data shall be stored and accessed in an ethical manner for data privacy and data protection.  An AI-powered keyword search methodology is suggested for locating pertinent data in the EHR's Big Data.